If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(-1 + 3a) = (15 + -5a) (-1 * -7 + 3a * -7) = (15 + -5a) (7 + -21a) = (15 + -5a) Remove parenthesis around (15 + -5a) 7 + -21a = 15 + -5a Solving 7 + -21a = 15 + -5a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '5a' to each side of the equation. 7 + -21a + 5a = 15 + -5a + 5a Combine like terms: -21a + 5a = -16a 7 + -16a = 15 + -5a + 5a Combine like terms: -5a + 5a = 0 7 + -16a = 15 + 0 7 + -16a = 15 Add '-7' to each side of the equation. 7 + -7 + -16a = 15 + -7 Combine like terms: 7 + -7 = 0 0 + -16a = 15 + -7 -16a = 15 + -7 Combine like terms: 15 + -7 = 8 -16a = 8 Divide each side by '-16'. a = -0.5 Simplifying a = -0.5
| 6+3x=-18+x | | -7(-1+-21a)=(15-25a) | | a-9=10 | | 6+z-8/4=9 | | 4(2x-5)-(3-x)=-17 | | 6=l^2-l | | 6=l^1-l | | 20=l^2-l | | -5*0-10y=50 | | 5x^2+6x=3 | | -h/12+5=-9 | | 4x-2(3x-7)=2(4+3x)+2 | | x-4/6=1.25 | | 2.9p=0.55 | | 16=-4+n/2 | | 8.31t=-100.812 | | 6x-8=6(2-3x) | | 4-2/6= | | 7x-1=2y+3 | | 6z-12=60 | | x/5+3=-18 | | 15b=10 | | -9*0-9y=81 | | 3y+16=52 | | 3p=41/5 | | 116-3y=6y-10 | | 7-2(m-4)=5 | | -5.3q=97.41 | | 2(m+3)=14 | | 8-5(2-7x)=0 | | x^2-4=21 | | x-12=x+4-2 |